Coming Full Circle: The Study of Big Business since 1950 - Klein, Maury (Enterprise & Society, 2001)
Taking a broad view of historians' work on the rise of big business in the United States over the last half-century, this article attempts to assess both where business history has been and where it may go in the future. The analysis recognizes the centrality of the impact made by Alfred D. Chandler, Jr., but it also delves into other paths, including some not taken, of interest to historians. This wide-ranging interpretation also maintains the importance of big business itself as a subject worthy of historical attention and argues that its crucial role in the development of American society has not yet been considered by mainstream historians with the intensity it deserves. Musing over the nearly constant preoccupation of practitioners with defining the scope of business history as a field, the essay highlights a number of topics needing attention, suggesting that historians of business are well positioned to shed light on the growing role of business in all aspects of life in the twenty-first century.
Keywords: Business History and gender